Essence and content of informational competence of a future sport coach - Kolyada, M. G.; Bugaeva, T. I.; Donichenko, E. Yu. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to reveal the essence and content of the information competence of the future sports coach.